Midwives' Experiences of Rural Maternal - Newborn Care in Ghana: A Phenomenological Inquiry - Mary Ani-Amponsah; Solina Richter (Rural Nurse Organization; Binghamton University, 2021)
Midwives' experiences of frontline healthcare delivery in rural maternal and newborn care have been minimally explored over the past two decades in low and middle-income countries but particularly in resource-limited settings, the situation is concerning. Understanding the dynamic influences that impact health care delivery in rural and remote settings is important for averting deaths, improving health outcomes and rural health care practice. Purpose: This study aimed to understand, unveil the meanings and articulate the experiences of midwives who practice in rural settings in rural Ghana. Sample: Thirteen (13) midwives who voluntarily participated in the study were purposively and conveniently sampled. Methods: Interpretive phenomenology that integrated African philosophy was used to explore and unveil the meanings embedded in the experiences of midwives practicing in South rural Ghana. Findings: The findings establish that midwives make sustained serial efforts to save maternal and newborn lives however, midwives' ethnic background, age, gender and family situation influence their retention in rural health care settings where they work alone under stressful conditions as skilled care birth attendants. Community recognition and supportive community participation positively impact midwives' practice in spite of unattractive living and working conditions. Future research needs to investigate the dynamic influences of chiefs, queen mothers and community leaders on emergency obstetric and newborn health care service delivery. Conclusion: The rural environment poses significant risks and barriers to safe and ethical health care delivery for women and newborns in Ghana. The intricate dynamics of midwives' age and family life, limited support in skilled care delivery and community participation influences midwives' intention to stay in rural practice. Keywords: Rural, Midwives, Pregnant Women, Labour, Newborns, Ghana DOI: https://doi.org/10.14574/ojrnhc.v21i2.654